PENGARUH AKUNTABILITAS PUBLIK, KEJELASAN SASARAN ANGGARAN DAN PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA SKPD DI PEMERINTAH DAERAH KOTA PALU - Asrini, Asrini (Katalogis, 2017)
This study aims to identify and analyze the Influence of Public Accountability, Goal Clarity Budget and Participation on Performance Budgeting SKPD Palu City Government. This research method using descriptive verification approach, the respondent is Pimpinanan SKPD in Palu City Government as many as 86 people. Methods of data analysis in this research is multiple linear regression analysis using a hypothetical test significant level Î± = 0.05 or Î± <0.05, Using SPSS version 16.00. The research proves that the value of Adjusted R-Square = 0.614 or 61.40% dependent variable is influenced by three variables are free, the rest of the independent variables is affected by other variables not studied, with the equation Y = 1.569 + 0,272X1 + 0,188X2 + 0,204X3 means the independent variables were analyzed in the form of a variable (X1, X2, and X3) to influence the dependent variable (Y) regression analysis model the performance of the SKPD in the city of Palu, where public accountability (X1) with tvalue 0.272 this translates into influence positive between public accountability and the performance of the SKPD. Budget goal clarity (X2) with 0.188 tvalue this means there is a positive influence between budget goal clarity and performance of the SKPD. Participation budgeting (X3) with 0.204 tvalue this means there is a positive influence between budgeting participation with the performance.